Keseimbangan Genetik Eksternal pada Ayam Hasil Silangan - Firman adam; Safriyanto Dako; Fahria Datau; Nibras karnain laya; Suparmin fathan; Ulfiani Saleh (Jambura Journal of Animal Science, 2020)
The purpose of this study was to determine the equilibrium of external genetic for the population of crossbreed chicken. Observations were made at the Poultry Production Unit Laboratory at Gorontalo State University. The focus was focused on the genetic equilibrium of the feathers covering the body, variations in coat color, calf color, and comb shape of the crossing population. Algebraic analysis (a + b = 1) was used to calculate phenotype frequencies, genes, and genes heterozygosity of feather color, feather pattern, shank color and comb shape for the cross chicken population. Analysis of genetic Equiblirium in the pattern of feather color, coat color, shank color, and comb shape in chicken populations was used the chi-square test. The genetic equilibrium for feather pattern can be achieved in the f2 generation. The f2 population found 3 feather color patterns: black, brown/light brown, and Columbia. Phenotype distribution; 9: 4: 3. The frequency of Genesis 0.157; 0.296; 0.546 and there was an increase in heterozygosity by 0.688 ± 0.121. The genetic equilibrium for comb shape is achieved in f1 and f2 generations. The genetic equilibrium for feather pattern can be achieved in the f2 generation.  The genetic equilibrium in cross-breed populations that have recessive/dominant homozygotes can be achieved in one generation while for cross-breeding chickens that have heterozygous properties, genetic equilibrium can be achieved in short generations if these traits are expressed evenly in the population.